Iminyl-Radical-Triggered C–C Bond Cleavage of Cycloketone Oxime Derivatives: Generation of Distal Cyano-Substituted Alkyl Radicals and Their Functionalization - Xiao, Tiebo; Huang, Hongtai; Anand, Devireddy; Zhou, Lei (Synthesis, 2020)
Alkyl nitriles are versatile building blocks in organic synthesis because the cyano group can be easily converted into other functional groups. Iminyl-radical-triggered C–C bond cleavage of cycloketone oxime derivatives provides a practical route to access distal cyano-substituted alkyl radicals, which has given chemists a new radical reaction platform for the synthesis of diverse alkyl nitriles. This review provides an overview of various types of radical cyanoalkylation via ring opening of cycloketone oxime derivatives.1 Introduction2 C–C Bond Formation2.1 Alkenes as Radical Acceptors2.2 Aromatic Rings as Radical Acceptors2.3 Organometallic Reagents as Radical Acceptors2.4 Cyanoalkyl-Radical-Triggered Cyclization Reactions2.5 Miscellaneous3 C–Heteroatom Bond Formation3.1 C–O Bond Formation3.2 C–N Bond Formation3.3 C–S Bond Formation3.4 C–Halogen Bond Formation3.5 C–B Bond Formation4 Conclusion
Keywords: iminyl radicals; C–C bond cleavage; cyanoalkylation; nitriles; single-electron transfer